Prevalence and trends of selected urologic conditions for VA healthcare users - Fischer Michael J; Taylor Brent C; Zhang Huiyuan; Sohn Min-Woong; Yano Elizabeth M; Saigal Christopher; Wilt Timothy J (BMC Urology, 2006)
Abstract Background Conducted as part of the Urologic Diseases in America project whose aim was to quantify the burden of urologic diseases on the American public, this study focuses on Veterans Health Administration (VHA) users as a special population to supplement data on overall prevalence rates and trends in the United States. Veterans comprise 25% of the male population 18 years or older and contribute substantially to the overall burden of urologic conditions. The objective of this study is to describe the prevalence rates and trends of urologic cancers and selected benign conditions from 1999 to 2002 for VHA users. Methods VHA administrative files for 1999 – 2002 and Medicare claims files for the same years were used to identify those who had a diagnosis of qualifying urologic conditions. Results Among the conditions evaluated, prostate cancer was listed as a primary diagnosis for 5.4% of VHA users in 2002, followed in decreasing prevalence by erectile dysfunction (2.9%), renal mass (1.5%), interstitial cystitis (1.4%), and prostatitis (1.1%). Age-adjusted rates showed significant increases for renal mass (31%), interstitial cystitis (14%), and erectile dysfunction (8%) between 1999 and 2002. Systematic variations in prevalence rates and trends were observed by age, race/ethnicity, and region. Those in the Western region generally had lower age-adjusted prevalence rates and their increases were also slower than other regions. Addition of Medicare data resulted in large increases (21 to 489%) in prevalence among VHA users, suggesting substantial amount of non-VA urological care provided to VHA users. Conclusion Prevalence rates for many urologic diseases increased between 1999 and 2002, which were not entirely attributable to the aging of veterans. This changing urologic disease burden has substantial implications for access to urologic care and treatment capacity, especially in light of the level of urologic care delivered to veterans by Medicare providers outside the VA. Further study on the factors associated with these increases and how they affect the patterns, cost, and quality of care in veterans is needed.